PERSEPSI MAHASISWA TERHADAP PENGGUNAAN QUIZIZZ DALAM PEMBELAJARAN AKUNTANSI KONSOLIDASI BANK SYARIAH DI IAIN PONOROGO - Muhtadin Amri; Yuz Arija Shobri (Universitas Negeri Padang, 2020)
This research aims to determine student perceptions of the effectiveness of the use of Quizizz as a game based learning applications. The population of the research is all 4th semester sharia banking students class of 2018. Respondents in this research is sharia Banking students who take sharia banking consolidation accounting course for the academic year 2019/2020. Total respondents in this research is 210 with total returned and could be analyzed questionnaires is 169. Data analysis performed using descriptive method which analyzed using quantitative and qualitative analysis. The research data was obtained by distributing surveys to all research samples using Google Forms application. The questionnaire instrument was measured using five likert scale, that is strongly disagree, disagree, not agree, agree and strongly agree.The results showed that in general students considered the use of Quizizz to have a positive impact in learning activities on the sharia banking consolidation accounting course. Students' consider Quizizz is easy-to use application, makes lectures more fun, increase mastery of the material, and increase students' motivation and activeness in studying sharia banking consolidation accounting course. There are some limitations and problems found in using Quizizz according to students', including internet connection limitations, the time limit given is too little, and some students also feel the need to discuss about the questions that are done through the Quizizz application in class so that answers are known which is correct and which is wrong.